2012
DOI: 10.13172/2050-2303-1-1-257
|View full text |Cite
|
Sign up to set email alerts
|

Surgical site infections subjected to photodynamic therapy: a potential application in orthopaedic surgery

Abstract: Introduction Photodynamic therapy, a minimally invasive oncological modality, has been in use for over 20 years. However, little clinical data is available on its non-oncological efficacy. Several laboratory-based trials on animals have suggested that this technology may be applicable as an antimicrobial therapy. In orthopaedics, where implants and metal work are placed in deep tissue planes, a potential risk of infection is treated very seriously. Infection not only increases patient morbidity and mortality b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Several in vitro studies have investigated the use of antimicrobial PDT and results are promising. Studies using various photosensitizers have demonstrated a complete bactericidal effect on a number of Gram-positive bacteria [ 22 ]. However, there appears to be a difference in susceptibility to PDT between Gram-positive and Gram-negative bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Several in vitro studies have investigated the use of antimicrobial PDT and results are promising. Studies using various photosensitizers have demonstrated a complete bactericidal effect on a number of Gram-positive bacteria [ 22 ]. However, there appears to be a difference in susceptibility to PDT between Gram-positive and Gram-negative bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of musculoskeletal injuries is often hard to manage, because these soft and hard connective tissues have low vascularity, healing rate and capability and tolerate stressful forces during the healing process, which increase complications [1][2][3][4] . Several reconstructive techniques and tissue engineering approaches have been introduced with the aim to restore the initial function at the injured area 2,5 ; however, due to the low healing capacity and several well-defined complications such as adhesions in the healing tendons, non-union and osteomyelitis in the healing bones, there is a need for accelerating the healing response in these tissues with the hope to improve the final outcome of the patients 2,[6][7][8][9][10][11][12][13] . Several healing promotive agents such as glycosaminoglycans and growth factors have been tested in animal studies with this purpose, but due to insufficient related clinical trials their clinical efficacy has not been well approved [6][7][8][9][10][14][15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%